RESPON MASYARAKAT MISKIN TERHADAP PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Jane Pratama Ardila; M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Health status of the poor are still in a low degree, caused by the difficulty of access to health services and health costs is still expensive. Government health insurance guarantees the poor to health services through the implementation of public health insurance program (Jamkesda) . Based on observations made , the length of time due to the large number of service registration enrolling patients not comparable with counter service capacity of Jamkesda. There are at least 40 patients had to wait before the counters opened. This study aimed to determine the profile of the poor who seek treatment in Duri General Hospital Kabupaten Bengkalis, and knowing the public response to the health services provided by the Hospital. Subjects of this study were visitors or patients Jamkesda that visited or went to the Duri General Hospital. There is also the number of respondents to be interviewed about 40 people. The data analysis technique used in this study is qualitative data analysis process begins by reviewing all data available through various sources, from interviews, observations that have been written in the recording field, documents, photo images and so on. The results stated that Jamkesda in Duri General Hospital Bengkalis is one of the government's efforts in improving and ensuring public health. The program is supported by funds from the budget and the state budget. Public response to the program Jamkesda in Duri hospitals is good enough, it can be seen from the large number of participants in the program Jamkesda spines reaching 9984 participants. Communities also benefit Jamkesda service that benefits both social and psychological benefits. Limiting factors of Jamkesda programs in Duri General Hospital is still a lack of socialization to the community so that there are still people who have not joined Jamkesda. Facilities and infrastructure that support the program, so that the program can not reach people in the area who have transportation difficulties.Keywords : Response , Service , Hospital